Utilization of medical treatments and adherence to antiretroviral therapy among HIV-positive adults with histories of childhood sexual abuse. - Meade, Christina S; Hansen, Nathan B; Kochman, Arlene; Sikkema, Kathleen J (AIDS patient care and STDs, 2009)
HIV is a chronic, life-threatening illness that necessitates regular and consistent medical care. Childhood sexual abuse (CSA) is a common experience among HIV-positive adults and may interfere with treatment utilization. This study examined rates and correlates of treatment utilization among HIV-positive adults with CSA enrolled in a coping intervention trial in New York City. The baseline assessment included measures of treatment utilization, mental health, substance abuse, and other psychosocial factors. In 2002-2004, participants (50% female, 69% African-American, M = 42.3 +/- 6.8 years old) were recruited. Nearly all (99%) received HIV medical care. However, 20% had no outpatient visits and 24% sought emergency services in the past 4 months. Among 184 participants receiving antiretroviral therapy (ART), 22% were less than 90% adherent in the past week. In a multivariable logistic regression model, no outpatient treatment was associated with African American race (AOR = 3.46 [1.42-8.40]), poor social support (AOR = 1.59 [1.03-2.45]), and abstinence from illicit drug use (AOR = 0.37 [0.16-0.85]). Emergency service utilization was associated with HIV symptoms (AOR = 2.30 [1.22-4.35]), binge drinking (AOR=2.92 (1.18-7.24)), and illicit drug use (AOR = 1.98 [1.02-3.85]). Poor medication adherence was associated with trauma symptoms (AOR = 2.64 [1.07-6.75]) and poor social support (AOR = 1.82 [1.09-2.97]). In sum, while participants had access to HIV medical care, a sizable minority did not adhere to recommended guidelines and thus may not be benefiting optimally from treatment. Interventions targeting HIV-positive adults with CSA histories may need to address trauma symptoms, substance abuse, and poor social support that interfere with medical treatment utilization and adherence.
Keywords: Adult; Ambulatory Care; Anti-HIV Agents; Child; Child Abuse, Sexual; Emergency Medical Services; Female; HIV Infections; Humans; Male; Middle Aged; Patient Compliance; Social Support